2014
DOI: 10.1186/1477-9560-12-14
|View full text |Cite
|
Sign up to set email alerts
|

Quality of vitamin K antagonist control and outcomes in atrial fibrillation patients: a meta-analysis and meta-regression

Abstract: Background: Atrial fibrillation (AF) patients frequently require anticoagulation with vitamin K antagonists (VKAs) to prevent thromboembolic events, but their use increases the risk of hemorrhage. We evaluated time spent in therapeutic range (TTR), proportion of international normalized ratio (INR) measurements in range (PINRR), adverse events in relation to INR, and predictors of INR control in AF patients using VKAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
97
1
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 108 publications
8
97
1
6
Order By: Relevance
“…Thus, underanticoagulation is more frequent than overanticoagulation in this global registry. This confirms the conclusion from a previous meta-analysis and meta-regression on quality of VKA control and outcomes in patients with AF where patients on VKA were frequently outside the target INR range and tended to be underanticoagulated rather than overanticoagulated [14]. …”
Section: Discussionsupporting
confidence: 89%
“…Thus, underanticoagulation is more frequent than overanticoagulation in this global registry. This confirms the conclusion from a previous meta-analysis and meta-regression on quality of VKA control and outcomes in patients with AF where patients on VKA were frequently outside the target INR range and tended to be underanticoagulated rather than overanticoagulated [14]. …”
Section: Discussionsupporting
confidence: 89%
“…Meta‐analyses of warfarin‐treated AF patients demonstrated 56% of measured INR to be within range and a TTR of 61% . Our study demonstrated superior control, with 73% of measured INR in the range of 2.0–3.0 and a mean TTR of 81%.…”
Section: Discussionmentioning
confidence: 54%
“…Por ello, la informació n del estudio PAULA ofrece datos de gran interé s. En el estudio PAULA, el 43,1% de los pacientes tenían en rango terapé utico menos del 60% de los controles realizados en el ú ltimo añ o y el 39,4% mostró un tiempo en rango terapé utico < 65%, con una media de 14,4 determinaciones por paciente. En un metaná lisis de 95 artículos, los pacientes anticoagulados con AVK se mantuvieron el 61% del tiempo en rango terapé utico, y fue mejor el control observado en ensayos clínicos o en clínicas especializadas que en otros escenarios 31 . Por lo tanto, se puede decir que el control de la anticoagulació n en Españ a es malo, algo similar a lo que ocurre en otros países.…”
Section: Discusió Nunclassified